Iranian Realist Manifestation in the Second Pahlavi Era - Moharran Rzayethy Kishekhaleh; Ali Safayi Sanghri; Seyyed Hasan Seyyed Nejad Jolodar (مطالعات زبانی و بلاغی)
The prominence of poetry of a period, and achieving a new style and language requires norm-evasion and abandoning the form, language, theme, subjects, and traditional useless images that this process was done in the poems of the second Pahlavi era due to various factors, especially the needs of Iranian society. This article, which named as Iranian Realist Manifestation in Second Pahlavi Era, has focused on studies on development and manifestation of Iranian realism by studying the poetry of this period in four subjects: social, political, partisan and religious. For this purpose, the authors began examining the nomadism and foregrounding, based on form-dealing and thematic look, and brought evidence from the poets of this era by explaining and analyzing the poems of the poets. They presented the most important elements of them by examples, and therefore they concluded that thematic normality and other forms of norm-evasion caused prominence of the poetry of this era and the manifestation and development of Iranian realism, which has different meanings and more prominent than other realism and a new identity for Iranian society and Persian poetry. The realism which has other signs, also has religious and sacred indications, the manifestations of which could be seen in the lives of the Iranian people as a great reality, and its effect on Persian poetry has caused prominence of it.